Perspectives de l'égalité juridique des langues au Canada - Yalden, Maxwell (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
A substantial gap exists between theory and practice in the area of linguistic equality. While it is widely accepted that Canada's two major linguistic groups should have equal access to services in their respective languages, difficulties arise in the application of this principle to concrete situations. From a theoretical point of view, the author recognizes that many reforms have been discussed promoting the goal of linguistic equality. While he admits that is unlikely that laws alone will guarantee the accomplishment of this objective, he indicates the areas where the laws are most likely to influence linguistic reality.